Convention and Reinvention: The British Library Shahnama of 1438 (Or. 1403). Issue 1 (2nd January 2019) - Firouzeh, Peyvand
ABSTRACT: The geographic origin of the fifteenth-century illustrated Shahnama manuscript Or. 1403, held at the British Library, has been the subject of unresolved scholarly debate. Stepping away from the binary alternatives that have been suggested for the attribution of the manuscript in the past (Iran versus India, and Delhi versus the Deccan), this essay focuses on text and image and their potential relationships in its preface-frontispiece set and how these would have addressed the manuscript's possible audiences. Evaluating the ways that the preface and frontispiece reimagine the established visual and textual conventions of Shahnama manuscripts in the fifteenth century, the study explores the manuscript's engagement with a range of possible socio-historical settings, all of which reflect the complex circulation and reception of Persianate modes of culture between Iran and India in this period.